2000
DOI: 10.2113/171.3.355
|View full text |Cite
|
Sign up to set email alerts
|

Integrated stratigraphy across the Paleocene/Eocene boundary in the Contessa Road section, Gubbio (central Italy)

Abstract: An integrated stratigraphic study of the upper Paleocene to lower Eocene Scaglia limestones of the Contessa Road section has allowed us to identify the classical markers of the Paleocene-Eocene transition. The section provides a good magnetostratigraphic record as well as a continuous calcareous nannofossil and foraminiferal biostratigraphy. A negative Carbon Isotopic Excursion (CIE) occurs in the lower part of Chron C24r. The calibration to calcareous plankton zonation indicates that the CIE occurs in the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…Umbria-Marche, Central Italy, Contessa Highway Section (Galeotti et al, 2000) Deep marine basin Pelagic sediments only identified during IETM A6 Galala Mountains, Egypt (Hontzsch et al, 2011;Speijer and Morsi, 2002;Speijer and Schmitz, 1998) Carbonate ramp and basin…”
Section: A5mentioning
confidence: 99%
“…Umbria-Marche, Central Italy, Contessa Highway Section (Galeotti et al, 2000) Deep marine basin Pelagic sediments only identified during IETM A6 Galala Mountains, Egypt (Hontzsch et al, 2011;Speijer and Morsi, 2002;Speijer and Schmitz, 1998) Carbonate ramp and basin…”
Section: A5mentioning
confidence: 99%
“…The interpretation of horizons with biserial agglutinated foraminifera (Spiroplecti nella, Textularia spp., Semivulvulina) is questionable because of poor knowledge of their ecological preferences in lower shelf-upper slope habitats. The biserial morphotypes are detritivorous bacterial scavengers adapted to a shallow to deep infaunal life strategy (Galeotti et al 2005;Nagy et al 2009). Shallow-water Textularia agglutinans is an opportunistic species and exhibits a preference for food-enriched conditions and a tolerance to oxygen deficiency (Barmawidjaja et al 1995), while Jorissen et al (1998) indicated that agglutinated foraminifera reflect oligotrophy on the sea-floor.…”
mentioning
confidence: 99%
“…The Palaeogene carbonate succession located in the Umbria -Marche (U -M) Basin in the northeastern Apennines of Italy is probably the most thoroughly studied in the Tethyan Realm, thanks to the accessibility of numerous well-exposed outcrops throughout this region, and its remarkable record of many crucial aspects of Earth's history from the Cretaceous -Palaeogene (K -Pg) boundary through to the uppermost Oligocene (Coccioni et al 1986(Coccioni et al , 1988(Coccioni et al , 1989(Coccioni et al , 2000(Coccioni et al , 2008(Coccioni et al , 2012Cresta et al 1989;Bellagamba & Coccioni 1990;Mattias et al 1992;Brinkhuis & Biffi 1993;Premoli Silva & Jenkins 1993;Lowrie & Lanci 1994;Montanari et al 1994Montanari et al , 1997Galeotti et al 2000Galeotti et al , 2004Galeotti et al , 2010Montanari & Koeberl 2000;Spezzaferri et al 2002;Coccioni & Galeotti 2003;Bodiselitsch et al 2004;Jovane et al 2004Jovane et al , 2006Jovane et al , 2007aJovane et al , b, 2009Jovane et al , 2010Brown et al 2009;Giusberti et al 2009;Hyland et al 2009;Pross et al 2010, and references therein).…”
mentioning
confidence: 99%